Graphic Propaganda And National Identity In Malaya (1948-1960) : A Social Semiotic Approach - Kuah, Li Feng (2009)
this research is essentially a study of graphic design history in Malaysia with the aim to generate more interest and future scholarship in this relatively unexplored area. Kajian ini pada dasarnya merupakan satu kajian sejarah seni grafik di Malaysia dengan matlamat untuk melahirkan minat dan kajian baru dalam bidang yang belum diceburi ini